Pre-treatment Drug Resistance Could Impact the 96-Week Antiretroviral Efficacy in Treatment-Naive HIV-1–Infected Patients in Guangdong, China - Pengle Guo; Yun Lan; Quanmin Li; Xuemei Ling; Junbin Li; Xiaoping Tang; Fengyu Hu; Weiping Cai; Linghua Li (​​​​​​​​Infectious Diseases & Immunity)
Abstract. Background. With the high prevalence of pre-treatment drug resistance (PDR) and the potential impact to the virological inhibition, the detection of PDR was particularly necessary. This study aimed to determine the prevalence of PDR in Guangdong, China, and its impact on antiretroviral therapy (ART) in treatment-naive HIV patients. Methods. A retrospective cohort study was conducted. A total of 1936 HIV-1–infected treatment-naive patients in the clinic of the infectious department, Guangzhou Eighth People’s Hospital, between August 2018 and December 2019 were assayed for PDR mutations before initiating ART. Patients with PDR mutations (PDR arm) were screened and compared with those without drug-resistant mutations (non-PDR arm). The rate of HIV-1 virologic failure (VF) and CD4+ T-cell counts of the 2 arms were compared at the 96th week after ART to evaluate the impact of PDR on the efficacy of ART. Results. Pretreatment drug resistance was detected in 125 cases (6.46%) from the 1936 enrolled participants, most of which were resistant to non-nucleoside reverse transcriptase inhibitors (64.00%, 80/125). One hundred and eight of 125 completed the follow-up of 96 weeks (PDR arm). In this cohort, 52 patients whose ART regimen containing the resistant drug were grouped as con-PDR arm, and the remaining 56 patients whose ART regimen did not contain the resistant drug were grouped as non- con-PDR arm. A total of 125 patients without PDR were randomly selected as the control group (non-PDR arm), 112 of whom had completed the 96-week follow-up. At the 96th week after ART initiation, 7 patients (6.5%, 7/108) in the PDR arm and 1 patient (0.9%, 1/112) in the non-PDR arm developed VF, exhibiting a significant difference (χ2 = 4.901, P = 0.029). Meanwhile, 3 patients (5.8%, 3/52) in the con-PDR arm developed VF; the rate was also higher than that in the non-PDR arm, but without a significant difference (χ2 = 3.549, P = 0.095). The CD4+ T-cell count in the non-PDR arm increased more than the PDR arm (386.6 vs. 319.1 cells/μL, t = 2.448, P = 0.015) or the con-PDR arm (386.6 vs. 325.1 cells/μL, t = 1.821, P = 0.070) at 12 weeks after ART. However, no significant differences were observed in the CD4+ T-cell count from the 24th week after ART onward. Conclusions. Pretreatment drug resistance was moderately prevalent in Guangdong, China, and could affect the antiretroviral efficacy during a 96-week observation period, indicating the need to closely monitor PDR before ART initiation.